Protective responses of older adults for avoiding injury during falls: evidence from video capture of real-life falls in long-term care - Robinovitch, Stephen; Dojnov, Aleksandra; Komisar, Vicki; Yang, Yijian; Shishov, Nataliya; Yu, Ying; Bercovitz, Ian; Cusimano, Michael D.; Becker, Clemens; Mackey, Dawn C.; Chong, Helen (Age & ageing, 2022)
falls are common in older adults, and any fall from standing height onto a rigid surface has the potential to cause a serious brain injury or bone fracture. Safe strategies for falling in humans have traditionally been difficult to study.to determine whether specific ‘safe landing’ strategies (body rotation during descent, and upper limb bracing) separate injurious and non-injurious falls in seniors.observational cohort study.two long-term care homes in Vancouver BC.videos of 2,388 falls experienced by 658 participants (mean age 84.0 years; SD 8.1) were analysed with a structured questionnaire. General estimating equations were used to examine how safe landing strategies associated with documented injuries.injuries occurred in 38% of falls, and 4% of falls caused injuries treated in hospitals. 32% of injuries were to the head. Rotation during descent was common and protective against injury. In 43% of falls initially directed forward, participants rotated to land sideways, which reduced their odds for head injury 2-fold. Upper limb bracing was used in 58% of falls, but rather than protective, bracing was associated with an increased odds for injury, possibly because it occurred more often in the demanding scenario of forward landings.the risk for injury during falls in long-term care was reduced by rotation during descent, but not by upper limb bracing. Our results expand our understanding of human postural responses to falls, and point towards novel strategies to prevent fall-related injuries.
Gesehen am 23.01.2023